Kesan intervensi kaunseling kelompok berstruktur adler ke atas persepsi terhadap keluarga, penghargaan kendiri dan kemurungan dalam kalangan remaja berisiko (IR) - Nasir Len (2009)
The purpose of this study was to assess the effects of Adlerian Group Counseling intervention in increasing perceptions toward family, self-esteem (peers self esteem and school self-esteem) and the reduction of depression of at risk adolescents. 40 subjects were choosen by using purposive sampling. Subjects were selected from Form 4 students of Sekolah Menengah Kebangsaan Spaoh, Betong, Sarawak. Subjects were placed into 2 groups, experimental group and control group. Research was done in 4 week with a total of 8 sessions. The quantitative data was collected based on pretest and post test self report measured by using the Adolescent Concern Evaluation (Springer, 1998). The data was analyzed and processed by using the SPSS-X Version 16.0 to analyze t-test at the significant level .05. The result of the t- test showed that there is a significant difference in the perceptions towards family, self-esteem and depression between the students that were involved and those who were not involved in the Adlerian Group Counseling. The finding suggests that Adlerian Group Counseling increases perceptions towards family, self-esteem and reduction of depression of at risk adolescents.